Molecular identification and antibiotic clearance of Mycoplasma arginini and Mycoplasma orale from cell cultures infected with Rickettsia or Ehrlichia species - Michelle E. J. Allerdice; Savannah L. Shooter; Maria F. B. M. Galletti; Joy A. Hecht; Sandor E. Karpathy; Christopher D. Paddock (Microbiology Spectrum)
ABSTRACT Mycoplasma (Class: Mollicutes) contamination in cell cultures is a universal concern for research laboratories. Some estimates report contamination in up to 35% of continuous cell lines. Various commercial antibiotic treatments can successfully decontaminate clean cell lines in vitro; however, in vitro decontamination of bacterial cultures remains challenging. Intracellular bacteria like those in the genera Rickettsia and Ehrlichia require cell culture for primary isolation and propagation and are thus vulnerable to contamination with mycoplasmas. Some analyses have reported successful antibiotic clearance of contaminating mycoplasmas in Rickettsia cultures; however, many of these studies do not identify the contaminating mycoplasma species and often include only a few isolates. To our knowledge, there are no published studies reporting decontamination of mycoplasmas from Ehrlichia cultures. In this study, we developed a specific multiplex assay to identify two of the most common mycoplasma culture contaminants, Mycoplasma arginini and Mycoplasma orale, in cell cultures infected with Rickettsia or Ehrlichia species. We further describe the successful in vitro decontamination of M. arginini, M. orale, and co-contaminations with both mycoplasmas from multiple Rickettsia and Ehrlichia cultures using daptomycin and clindamycin.IMPORTANCEMycoplasma contamination is a frequent problem in bacterial cell culture. These prolific organisms thrive in the extracellular environment in vitro and can persist in cell lines indefinitely without treatment. Historically, mycoplasma-contaminated Rickettsia cultures were cleared of contaminants by inoculating laboratory mice and re-isolating mycoplasma-free Rickettsia from brain endothelial cells. However, this method requires the sacrifice of live animals and is not always effective. Mycoplasma clearance via mouse inoculation requires a patent infection of murine central nervous system endothelial cells, which may not occur with some mildly pathogenic or nonpathogenic rickettsial species. In vitro antibiotic treatment represents an alternate method to eliminate contaminating mycoplasmas from rickettsial cultures. This method requires minimal adjustment of laboratories that already maintain rickettsial cultures and is not dependent on the use of laboratory animals. As such, the comprehensive strategy for Mycoplasma arginini and Mycoplasma orale elimination presented here can improve laboratory efficiency for in vitro research with intracellular bacteria.